2004
DOI: 10.1002/ajmg.a.30296
|View full text |Cite
|
Sign up to set email alerts
|

Two patients with monomelic ulnar duplication with mirror hand polydactyly: Segmental Laurin–Sandrow syndrome

Abstract: We have studied two unrelated boys with isolated left mirror hand and ulnar duplication. Neither had facial anomalies and family histories were unremarkable. We suggest that these boys have segmental Laurin-Sandrow syndrome, or mirror-image duplication, due to somatic mutation involving precursor cells of the left upper limb and that the facial and digital abnormalities in Laurin-Sandrow syndrome are consistent with ectopic anterior hedgehog signaling in the developing limb bud and in the maxillary processes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…It has been previously suggested that LSS shares many similarities with Dbf and may also arise from ectopic IHH expression (Innis and Hedera, 2004). To investigate the possibility that Dbf and LSS share a common etiology, we screened five patients diagnosed with LSS for copy number variation at 23 sites between IHH and EPHA4 using multiplex ligation-dependent probe amplification (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously suggested that LSS shares many similarities with Dbf and may also arise from ectopic IHH expression (Innis and Hedera, 2004). To investigate the possibility that Dbf and LSS share a common etiology, we screened five patients diagnosed with LSS for copy number variation at 23 sites between IHH and EPHA4 using multiplex ligation-dependent probe amplification (see Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…Many patients with monomelic or unilateral anomalies similar to those seen in LSS have been described [Pintilie et al, 1964; Viljoen and Kidson, 1990; Rambaud‐Cousson et al, 1991; Skoll et al, 2000; Al‐Qattan et al, 2002; and 13 more cases reviewed by Innis and Hedera, 2004]. Some authors have considered these cases to represent segmental forms of LSS [Innis and Hedera, 2004], and theories including “postzygotic mosaicism” have been proposed to explain their occurrence. In contrast, others think that phenotypic differences may reflect different entities related pathogenetically [Hersh et al, 1995; Kantaputra, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are important genes determining the normal tetrapod limb pattern ( HoxD , BMP‐2 , BMP‐4 ) or the pentadactyl digit formula ( Shh or Ihh ), but their real contribution to the development of LSS has been discarded or remains to be determined [Hersh et al, 1995; Kim et al, 1997; Vargas et al, 1998; Innis and Hedera, 2004]. An additional set of genes has been proposed given the anomalies similar to LSS presented by transgenic mice and chicks: Hoxb‐8 [Charité et al, 1994; Hatchwell and Dennis, 1996; Kantaputra, 2001; Innis and Hedera, 2004], Lst [Van Steensel, 1997], Alx4 , Gli3 , dHAND , Hoxd12 , Dbf [Innis and Hedera, 2004], Fgf4 and Fgf8 [Kjaer et al, 2005]. Finally, two genes RAR‐B and RAR‐G had been considered given their relation to nose and limb formation, with unsatisfactory results [Kjaer et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meist wird über Einzelfälle berichtet, nur zweimal über die Behandlung zweier Patienten [4,5] und es gibt eine Studie, die über 7 Behandlungen von 7 Patienten in 7 Zentren berichtet [2].…”
Section: Die Mirror-hand Oder Ulnare Dimelie Eine Sehr Seltene Fehlbunclassified